Perancangan dan Pembuatan Sistem Penebusan Obat Berbasis Website di Instalasi Farmasi RSIA Muhammadiyah Kota Probolinggo - Arga Kanya Dhanastra; Mochammad Choirur Roziqin; Novita Nuraini; Angga Rahagiyanto (Indonesian Journal Publisher, 2024)
The long waiting time is due to the large number of prescriptions that must be served by the staff, the writing of the prescription is unclear and incomplete (for example: dose, amount, and patient name) so that the pharmacy staff must confirm it first with the doctor who wrote the prescription, this is because Doctors' knowledge of the availability of medicines is not well confirmed and doctors write prescriptions for medicines that are difficult for staff and patients to understand if they want to redeem medicines again. To overcome this problem, a drug redemption information system is needed. Research and development with data collection through interviews, observation, and documentation was used as the research method. The development method used is waterfall by pressman which consists of the stages of system requirements analysis, system design, coding and testing. This research produces a website-based drug redemption information system at the RSIA Muhammadiyah pharmacy installation in Probolinggo City which has advantages including redeeming medication electronically using a prescription given by a doctor, medication redemption can be done anywhere and then you can choose to pick it up at the hospital or have it delivered. Home, chat with pharmacists in real time which aims to make it easier for patients to ask questions about medicines, and electronic prescriptions to reduce prescriptions that are difficult to read.